ELECTRONIC QUESTIONNAIRE SYSTEM FOR THE COLLECTION OF RESEARCH DATA WITHIN THE FRAMEWORK OF LMS - KLEMENT, Milan; STENCL, Jiri (Journal of Technology and Information Education, 2012)
The present essay puts forward a draft of the process for designing and building an electronic questionnaire system usable for collecting research data. These data can then be applied within the framework of statistical processing using computational techniques, such ass multidimensional methods of cluster and factor analysis. The introduced system has been applied in practice in order to collect research data within the project GA CR No. P407/11/1306 - Evaluation of educational materials for distance learning and e-learning.
Keywords: e-learning; research surveys; research data; research questionnaire; electronic questionnaire; database